A NEW LOOK AT THE HISTORY OF THE ART OF PATCHWORK - Arzu Aslan qızı Sadiyeva (Theoretical Hypotheses and Empirical Results, 2023)
Patchwork pattern type is an ancient type of embroidery and it is an embroidery method that consists of riveting different parts of fabric to each other. This type of art was popular in the Middle Ages among the inhabitants of Ancient Egypt, India, Russia, Byzantium, as well as ancient Iran and medieval Europe. In Azerbaijan, it can be found in Absheron, Ganja, Gazakh and Gadabey regions. In this article, Western and Eastern patchwork art forms are analyzed.